2017
DOI: 10.1590/s1518-8787.2017051006808
|View full text |Cite
|
Sign up to set email alerts
|

Working hours and health in nurses of public hospitals according to gender

Abstract: OBJECTIVETo assess the association between weekly working hours and self-rated health of nurses in public hospitals in Rio de Janeiro, State of Rio de Janeiro, Brazil.METHODSA total of 3,229 nurses (82.7% of the eligible group) participated in this cross-sectional study, carried out between April 2010 and December 2011. The collection instrument consisted of a self-administered multidimensional questionnaire. The weekly working hours were calculated from a recall of the daily hours worked over seven consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
1
13
1
7
Order By: Relevance
“…It is possible this is a way to benefit older workers who have worked longer in the facility, because the night shift has fewer demands compared to the day shift and higher salaries 4 . Even though there is some indication that recently graduated young and single workers with fewer years of experience 24 work on the night shift, recent studies report results similar to this study 2 , 25 .…”
Section: Discussionsupporting
confidence: 71%
“…It is possible this is a way to benefit older workers who have worked longer in the facility, because the night shift has fewer demands compared to the day shift and higher salaries 4 . Even though there is some indication that recently graduated young and single workers with fewer years of experience 24 work on the night shift, recent studies report results similar to this study 2 , 25 .…”
Section: Discussionsupporting
confidence: 71%
“…Although this investigation did not find a significant difference in the odds ratio between the different working days, the study showed higher prevalence of illness among workers with long working hours (26) . The illness resulting from long working days can be explained by the reduction of free time -for sleep and recovery, family and social experience in addition to the longer exposure time to the risks of illness limited to the work environment (27) . This aspect was reported by nurses in qualitative research, when they attributed the illness to work overload and lack of time for self-care (28) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in order to assure their place in the contemporary world, nurses need to work harder, which harms their lifestyle both in professional and social spheres, and makes the achievement of personal desires difficult. By working exhaustively, there is no time for leisure, social relationships, varied activities, and especially for self-care (physical or mental) (14) .…”
Section: Discussionmentioning
confidence: 99%